Flame-retardant hybrid materials based on expandable polystyrene beads. (May 2020) - Reuter, Jens; Standau, Tobias; Altstädt, Volker; Döring, Manfred
A highly efficient flame-retardant hybrid foam material combining expandable polystyrene foam beads and a waterborne resin equipped with inorganic flame retardants is described. The resin and the inorganic fillers were varied, and the different compositions were investigated in small burner and cone calorimeter tests. The burning time during the small burner test decreases from >60 s for neat expandable polystyrene to 0 s for optimized hybrid specimens. The peak of the heat release rate decreases from 661.0 kW/m 2 for neat expandable polystyrene to 121.36 kW/m 2 for a hybrid composition of 1:1:1 (expandable polystyrene:aluminum hydroxide:phenol formaldehyde resin). The hybrid materials containing inorganic flame retardants are burning slower and release heat and smoke more constantly at significantly lower rates. Furthermore, a continuous network of the cured thermoset is shown, which leads to embedded expandable polystyrene beads. The flame-retardant thermoset protects the expandable polystyrene from fire and leads to a material with high dimensional stability and efficient flame retardancy.